All contraindications to thrombolysis for life-threatening pulmonary embolus should be considered relative. (10th December 2013) - Mercer, Rachel M; Bowen, Jordan S T; Armstrong, Richard J
Abstract : Acute massive pulmonary embolism (PE) can be fatal; however, timely thrombolytic therapy can be life saving. Guidelines advocate the use of thrombolysis for massive PE in patients with an acceptable bleeding-risk profile. Nonetheless, estimating what constitutes an acceptable bleeding risk in those with life-threatening PE is a clinical challenge, and even contraindications considered 'absolute' may present lesser risk than leaving PE untreated. We discuss the case of a 77-year-old man who received thrombolysis for a massive PE 4 weeks following admission with a significant intracerebral bleed. There was rapid resolution of hypotension and hypoxia and he survived to be discharged home. This case is used to illustrate that no potential therapy should be discounted in patients faced with acute life-threatening PE. Decisions to thrombolyse patients with traditional contraindications—even those considered absolute—must be taken by clinicians able to weigh relative risks.